Etiology of acute otitis media and serotype distribution of Streptococcus pneumoniae and Haemophilus influenzae in Chilean children <5 years of age - Rosenblut, Andres (Medicine (Baltimore), 2017)
The impact of bacterial conjugate vaccines on acute otitis media (AOM) is affected by several factors including population characteristics, bacterial etiology and vaccine conjugation method, carrier, and coverage. This study estimated the baseline etiology, distribution, and antibiotic susceptibility of bacterial serotypes that causes AOM in children aged <5 years in a public setting in Santiago, Chile. Children aged ≥3 months and <5 years referred to the physician for treatment of AOM episodes (with an onset of symptoms <72 h) were enrolled between September 2009 and September 2010. Middle ear fluid (MEF) was collected by tympanocentesis or by otorrhea for identification and serotyping of bacteria. Antibacterial susceptibility was tested using E-test (etrack: 112671). Of 160 children (mean age 27.10 ± 15.83 months) with AOM episodes, 164 MEF samples (1 episode each from 156 children; 2 episodes each from 4 children) were collected. Nearly 30% of AOM episodes occurred in children aged 12 to 23 months. Streptococcus pneumoniae (41.7% [58/139]) and Haemophilus influenzae (40.3% [56/139]) were predominant among the cultures that showed bacterial growth (85% [139/164]). All Streptococcus pneumoniae positive episodes were serotyped, 19F (21%) and 14 (17%) were the predominant serotypes; all Haemophilus influenzae strains were nontypeable. Streptococcus pneumoniae were resistant to penicillin (5%) and erythromycin (33%); Haemophilus influenzae were resistant to ampicillin (14%) and cefuroxime and cefotaxime (2% each). AOM in Chilean children is predominantly caused by Streptococcus pneumoniae and nontypeable Haemophilus influenzae. Use of a broad spectrum vaccine against these pathogens might aid the reduction of AOM in Chile.